DIRECTIVE SPEECH ACTS IN THE SHORT STORY OF DJAKA LODANG MAGAZINE JANUARY TO MAY 2021 EDITION - Inayah, Septu (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2022)
This study aims to describe the types of directive speech acts and the function of directive speech acts contained in the short story of Djaka Lodang magazine from January to May 2021 edition. This type of research is a qualitative descriptive study. The data in this study are in the form of quotations contained in short stories. The source of the data is the short story from the January to May 2021 edition of Djaka Lodang magazine. The data were collected using library research and note-taking techniques. Furthermore, it is analyzed through the content analysis method. The results of the analysis are presented in an informal way. This informal method is used to describe the types of directive speech acts and the function of directive speech acts contained in the short story of Djaka Lodang magazine January to May 2021 edition. The results of the directive speech act analysis in the short story of Djaka Lodang magazine January to May 2021 edition are the types of acts directive speech and the function of directive speech acts. The results of the analysis include 6 directive speech acts including the speech acts of inviting 10, asking for 10, ordering 7, requesting 4, suggesting 4, and commanding 10. Of the six types of directive speech acts contained in the short story of Djaka Lodang magazine January to May 2021 edition, each of which has the function of the directive speech act of inviting, asking, ordering, pleading, and suggesting, each of which has the purpose of carrying out an action mentioned in the speech in the short story of Djaka Lodang magazine January to May 2021 edition.